PROFESSOR LEV SKVORTSOV'S DICTIONARIES OF THE RUSSIAN LANGUAGE - A. R. Blagova (Концепт: философия, религия, культура, 2019)
This article focuses on the work of Professor Lev Ivanovich Skvortsov as a lexicographer, explores the main dictionaries he was involved in as a creator and an editor, as well as new dictionaries composed by Professor Skvortsov himself, characterizes them and establishes their practical value.Standard dictionaries, including spelling dictionaries, dictionaries of grammatical Russian speech and explanatory dictionaries are most demanded in the society. The Large Spelling Dictionary of the Russian Language (BOS), containing more than 106,000 words, under the editorship of Stepan Barkhudarov, Ivan Protchenko and Lev Skvortsov, continue the heritage of academic Spelling Diction ary of the  Russian Language published in 30 editions. The new dictionary included a lot of recent terms from various areas of knowledge as well as data from modern everyday speech.Many years of language observation resulted in the Large Explanatory Dictionary of Grammatical Russian Speech (8,000 words) dated 2005, 2006 and 2016. It became popular among experts and all people interested in issues of correct speech. This is an explanatory dictionary of prescriptive and stylistic kind first introduced in the Russian lexicography. It served as a basis for a more compact School Dictionary on Culture of Spoken Russian. As for the general reader, the “Culture of Spoken Russian” dictionary by Professor Lev Skvortsov, reissued and revised, was introduced. This is an all-purpose dictionary on pronunciation and stress, formation of grammatical forms and structures, verb and nominal government, word building and phraseology, containing 3,000 entries.Speaking of the main explanatory dictionaries, we cannot overlook the Explanatory Dictionary of the Russian Language by Sergey Ozhegov, which runs through numerous editions. One of the recent editions, the 25th one, has been issued in 2006 under the editorship of Professor Skvortsov; it contains around 65,000 words and idioms. This edition of the dictionary includes a fair amount of new words and expressions (more than 3,000) reflecting changes in social and political, scientific, and cultural life of Russia. Moreover, modern linguistic processes were also taken into account. Professor Skvortsov worked on bringing Ozhegov’s dictionary closer to present days.The last and the most significant work of Professor Skvortsov was the Large Explanatory and Expository Dictionary of the Russian Language. Despite it wasn’t finished, the materials collected were enough to publish the first volume. It represents a new kind of explanatory dictionary of the Russian language. The author noted this himself, emphasizing that that was the new type of dictionary which “together with proper linguistic data also includes general historical and terminological knowledge, details from everyday life and extralinguistic information”.The article ends with a conclusion that Professor Skvortsov performed a tremendous task, leaving us a vast linguistic heritage. His remarkable diligence, wealth of knowledge and love for his native Russian language made it possible. His dictionaries listed above are of great importance: all of them undoubtedly help their readers to raise their level of Russian proficiency, to speak and to write correctly; these dictionaries can be immensely useful in classes of Modern Russian, Culture of Speech, and Practical Stylistics. Everybody - especially students and experts, both in humanities and engineering areas - would benefit from using these dictionaries.